Clinicopsychological profile of children with bleeding disorders from a tertiary center in Karnataka - Varadarajan, Meera; Rakesh, S R; Ramaswamy, Premalatha; Mohammed, Raj; Ramiah, Smita (Indian Journal of Child Health, 2017)
Objectives: The aim of this study is to observe the clinical spectrum of presentation of hemophilia and other bleeding disorders in children. Material and Methods: This observational study was carried out in the Comprehensive Hemophilia Center at Bangalore Medical College and Research Institute from December 2015 to August 2016. Clinical profile of 126 diagnosed children of hemophilia and other bleeding disorders <18 years of age was analyzed. Results: Among the 126 cases of bleeding disorders, 123 were male and 3 were female. 101 (80.2%) cases were of hemophilia A, 15 (11.9%) cases were hemophilia B, and 3 (2.4%) were of Von Willebrand disease. Other rare deficiencies were seen in 7 (5.5%) cases. Mean age at diagnosis was 2.5 years (range-1 month to 8 years). Only 45.2% of cases had a family history of bleeding. Inhibitors were seen in 9 (7.14%) cases with hemophilia A. Joint bleeding (52.9%) either spontaneous or after trauma was the main forms of bleeds with hemarthrosis of knee joint being most common. Psoas muscle bleeds in 10 (33.3%) followed by hematemesis and melena in 7 (23.3%) were the most common critical bleed seen in our patients. Numerous psychosocial issues such as school absenteeism (68.25%), family dysfunction (50.8%), depression, low self-esteem, parental separation (21.4%), and divorce (2.4%) were noticed. Mothers were blamed for the disease and victimized in 10 (7.9%) cases. Conclusion: Joint bleeding was the most common bleed with hemarthrosis of knee joint being the major presentation. Psoas muscle bleeds were the most common critical bleed. Major life-threatening bleeds such as intracranial bleed and liver bleeds were seen only in patients with severe hemophilia A. Numerous psychosocial issues were noticed quite often and need equal attention as a medical treatment to optimize hemophilia care.